2008
DOI: 10.1021/ac801842q
|View full text |Cite
|
Sign up to set email alerts
|

Chemiluminescence Detector with a Serpentine Flow Cell

Abstract: We present a new chemiluminescence detector, with solution channels that have been machined into a Teflon disk and sealed with a sapphire window. The configuration of the flow cell can be conveniently modified by replacing the Teflon disk. A comparison of some existing and novel designs, using the chemiluminescence reaction of morphine with acidic potassium permanganate and the bioluminescence reaction of ATP with the commercially available "BacTiter-Glo" reagent, has revealed that a serpentine channel allows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
68
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 24 publications
0
68
0
Order By: Relevance
“…[1,5] To the best of our knowledge the redox potentials of the short-lived radical excitation sources are not known, so a comparison of E 0 values is not possible. Nevertheless, to confirm the relevance of our EPR experiments (Figures 1 and 4) to the disparate detection limits reported [1,5] for these model excitation/quenching substrates (Scheme 1), we measured the emission from [RuA C H T U N G T R E N N U N G (bipy) 3 ] 2 + * using flow injection analysis (FIA) methodology, in which the [RuA C H T U N G T R E N N U N G (bipy) 3 ] 3 + /alkaloid chemiluminescent reaction was now initiated within a dual-inlet serpentine flow-cell [20] mounted flush against a photomultiplier tube housed in a light-tight container. The results of these experiments (Table 1) are in complete agreement with earlier mentioned studies, [1,5] where we have observed that the response for 10 À7 m codeine (248 mV) was greater than that recorded for 10 À4 m morphine (44 mV) despite the three orders of magnitude lower concentration of the former.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1,5] To the best of our knowledge the redox potentials of the short-lived radical excitation sources are not known, so a comparison of E 0 values is not possible. Nevertheless, to confirm the relevance of our EPR experiments (Figures 1 and 4) to the disparate detection limits reported [1,5] for these model excitation/quenching substrates (Scheme 1), we measured the emission from [RuA C H T U N G T R E N N U N G (bipy) 3 ] 2 + * using flow injection analysis (FIA) methodology, in which the [RuA C H T U N G T R E N N U N G (bipy) 3 ] 3 + /alkaloid chemiluminescent reaction was now initiated within a dual-inlet serpentine flow-cell [20] mounted flush against a photomultiplier tube housed in a light-tight container. The results of these experiments (Table 1) are in complete agreement with earlier mentioned studies, [1,5] where we have observed that the response for 10 À7 m codeine (248 mV) was greater than that recorded for 10 À4 m morphine (44 mV) despite the three orders of magnitude lower concentration of the former.…”
mentioning
confidence: 99%
“…Perhaps more importantly, the results of this study address the dearth of spectro- [11] of Figure 4 a with the spin Hamiltonian H = g iso bBS + S j a j SI j and spin Hamiltonian parameters described in the text. (1 mm, 0.05 m H 2 SO 4 ) was injected into an acidic aqueous carrier stream (0.05 m H 2 SO 4 ) that merged with a flowing substrate stream (no acid) within a dual-inlet serpentine reaction zone [20] of a GloCel detector with an extended range PMT module (N.D. = not detected, S = detector saturated). Responses shown are the signal after subtraction of the "blank" (14 mV) observed when the substrate stream is replaced with deionised water.…”
mentioning
confidence: 99%
“…Studies by our research group and others have shown: (1) repeated changes in the direction of solution flow (such as reversing turns) enhances the mixing efficiency and therefore the emission intensity [12,19,20,22]. (2) Relatively large chambers or wells in the detection zone generally delay the onset of the maximum emission as the solution rapidly moves through the path of least resistance, leaving surrounding areas of poor solution mixing [19,21]. (3) Channels machined or etched into an opaque white polymer and sealed with a thin piece of transparent material minimise the loss of light through surfaces not exposed to the photodetector [17,20,23].…”
Section: Introductionmentioning
confidence: 99%
“…For his research in these areas, he has received a Victoria Young Tall Poppy Science Award (Australian Institute of Policy and Science), the Robert Cattrall Medal (Royal Australian Chemical Institute) and the Gordon F. Kirkbright Award (Association of British Spectroscopists). machining channels into polymer materials has enabled exploration of designs that are not accessible using the traditional coiled-tubing approach [12][13][14][15][16][17][18][19][20][21]. Studies by our research group and others have shown: (1) repeated changes in the direction of solution flow (such as reversing turns) enhances the mixing efficiency and therefore the emission intensity [12,19,20,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation